Fluorescent molecular spring that visualizes the extension and contraction motions of a double-stranded helicate bearing terminal pyrene units triggered by release and binding of alkali metal ions. Issue 80 (20th September 2019) - Taura, Daisuke; Shimizu, Kaori; Yokota, Chiaki; Ikeda, Riho; Suzuki, Yoshimasa; Iida, Hiroki; Ousaka, Naoki; Yashima, Eiji
Abstract : A unique springlike motion of a fluorescent pyrene-terminated double-stranded helicate is visualized by the catch and release of alkali metal ions. Abstract : A novel double-stranded spiroborate helicate bearing terminal pyrene residues exhibited reversible fluorescence color changes (green and blue colors) due to the unique unidirectional springlike motions of the helicate triggered by catch and release of alkali metal ions.